Microplastic Detection in the Blood of Female Waste Workers at Landfill Site - Amalia Putri Kurniawati; Marshanda Rachma Maulida; Muhammad Alvin Alvianto (ECOTON: Ecological Observation and Wetlands Conservation, 2026)
Microplastics constitute an emerging environmental health concern, as their presence has been confirmed in human blood, with potential implications for adverse health outcomes, particularly among occupationally exposed populations. This study was conducted to identify the presence of fragment-type microplastics in human blood and to observe their relationship with individual characteristics (age, length of employment, and type of work) in a group of female scavengers. A total of 24 blood samples were analyzed using the blood smear method and observed under a binocular light microscope. The results showed that all samples contained microplastic fragments. Statistical analysis using the chi-square test on variables such as age, length of employment, and type of work did not show a significant association with the presence of microplastics. Stricter monitoring and control of plastic exposure in landfill environments are needed, along with occupational health protection for vulnerable waste pickers. Additionally, further research using more advanced chemical analysis methods and a larger sample size is important to strengthen the findings and identify potential long-term health risks.